Performance of hydrailic coagulation and flocculation of sg kampar water treatment plant - Mohammad Helmi bin Buang, Mohammad Helmi (2009)
The objective of the study is to assess the influent of physical and other variables such as flow rate, temperature, dosage of alum and pH on the performance of hydraulic coagulation and flocculation of Sg. Kampar Water Treatment Plant.